Letter to the Editorial Office: How to Shape Conciseness for Ecology and Sustainable Development? - Sztumski, Wiesław (Problemy Ekorozwoju, 2011)
I am in favor of shaping the eco-awareness of specific individuals, not the abstract eco-awareness of society. To this end, in order to achieve a temporary improvement in the condition of our environment, at least in the first phase, until compliance with the law becomes a habit and moral norm, sanctions for non-compliance with environmental standards should be significantly tightened, because nothing affects people’s behavior more than the fear of punishment. Only later, after achieving a sufficiently high degree of eco-awareness, can legal requirements be replaced by moral obligations. At the same time, conduct systematic and permanent (and not occasional from a great holiday) pro-ecological education. Education through persuasion and persuasion should also be used.